Colonic Cancer and Acromegaly - Dworakowska, Dorota; Grossman, Ashley B. (Frontiers in Endocrinology, 2019)
Acromegaly results in a significantly increased morbidity and mortality due to cardiovascular and respiratory complications as well as malignancies arising mainly from the colon. Furthermore, an increased lifetime risk of malignant transformation of pre-malignant colonic lesions relates to a worse overall prognosis from colorectal cancer, which is currently considered a major disease related complication. In this review we provide some insight into colonic changes in this condition, summarise current knowledge and evidence on the use of colonoscopic screening in patients with acromegaly, and suggest a recommended screening protocol.